Annual meeting of the Japanese pharmacological society - Bakar, Ruzilawati Abu (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2012)
High-performance liquid chromatography (HPLC) was compared with gas chromatography-mass spectrometry (GCMS) for determination of morphine in human urine. Calibration standards were prepared In human urine. Codeine and d3-morphine were added as the Internal standards for HPLC and GCMS. respectively. After solidphase extraction, the reconstituted samples were divided rnto aliquots for analysis br HPLC and GCMS. The analytical performances o the two methods were compared with regard to sensitivity, precision and accuracy. Results Indicated that tfPlC analysis produced results at least as precise, accurate and specific as GCMS for morphrne. Thus, analytical results by HPLC were comparable to GCMS. Therefore. HPLC can be useful alternative to GCMS for measuring morphine in urine.